IMPLIKASI AMANDEMEN UNDANG-UNDANG DASAR 1945 TERHADAP SISTEM PERENCANAAN PEMBANGUNAN NASIONAL - SOFIA L. ROHI, SOFIA L. ROHI (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
ABSTRACT 1945 amendments give rise to changes in various aspects of community life in Indonesia in general, including changes to the national planning system. National development planning system is understood as a state in formulating a framework of activities to be carried out for short term, medium term and long term. National development planning system was implemented at various levels of state government at both local (regional) and central government level. The method used for writing this thesis is the type of research used is normative, ie research that is focused on reviewing the principles, rules and norms of positive law, especially relating to the implications of the 1945 Amendment to the national development planning strategy. Used approach is the approach of law (statute approach). Processing of legal materials in this study is an inventory of legal materials, legal materials classification and systematization of legal materials. National development planning and practice has been known since the Homeland which was formed with the authority of the Assembly prepare and establish guidelines, to be implemented by the President as the mandatory Assembly, including all state institutions, because prior to the 1945 amendment of the MPR is positioned as the highest state body and the Assembly can distribute authority to all state agencies both vertically and horizontally between the central and local governments within the framework of the Homeland. However, after the 1945 amendment either content/substance of the 1945 changes was to eliminate the authority of the Assembly to prepare and establish guidelines, so that all the good administration of the state executive, legislative and judicial branches have a development plan states independently and put the vision, mission and work program of the president chosen to target the country's development planning. Keywords: National Development Planning System, Implications, Amendment UUD 1945